2006
DOI: 10.1159/000095467
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Levels in Rural Thai and Urban Singaporean Homes

Abstract: Background: Exposure to dust endotoxin and allergens in early childhood may influence the development of allergic diseases. Aims: This study aimed to evaluate dust endotoxin and dust mite allergens in urban Singapore and rural Thai homes of young children and study potential environmental influences. Methods: Mattress dust endotoxin and Der p 1, Der f 1, group 2 (Der f 2 and Der p 2) and Blo t 5 allergen levels were quantified in 101 infant mattress dust samples, 51 from urban Singapore and 50 from rural Thail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…For example, studies from farms in Europe show an inverse relationship between environmental endotoxin levels and the prevalence of hayfever, atopic wheeze and atopic sensitization [40]. Our group has demonstrated higher home endotoxin levels in rural South Thailand compared with urban Singapore, where higher prevalences of asthma, allergic rhinitis and eczema are seen [41]. Apart from external microbial exposure, differences in gut microflora may also play a role.…”
Section: What Are the Possible Causes For The Difference In Epidemiolmentioning
confidence: 49%
“…For example, studies from farms in Europe show an inverse relationship between environmental endotoxin levels and the prevalence of hayfever, atopic wheeze and atopic sensitization [40]. Our group has demonstrated higher home endotoxin levels in rural South Thailand compared with urban Singapore, where higher prevalences of asthma, allergic rhinitis and eczema are seen [41]. Apart from external microbial exposure, differences in gut microflora may also play a role.…”
Section: What Are the Possible Causes For The Difference In Epidemiolmentioning
confidence: 49%
“…This finding is similar to those of previous longitudinal studies for eczema 28 and asthma, 29 but to our knowledge, this is the first study to prospectively examine this relationship for the development of food allergy. Previous studies have demonstrated that endotoxin levels are lower in urban environments than in rural farming areas, 30,31 and a recent study examining the indoor microbiome in the same URECA cohort found that exposure to specific allergens and bacteria was associated with reduced sensitization to inhalant allergens as well as recurrent wheeze (in press). Therefore, while it has been previously suggested that the high rates of allergy and asthma in the inner city contradict the hygiene hypothesis, 32 both of these studies suggest that this is not actually the case.…”
Section: Discussionmentioning
confidence: 98%
“…There was one study that examined sensitization in Thai children suffering from allergic rhinitis, reporting that the predominant aeroallergen to which patients were sensitized in Bangkok was house dust mite [60]. A subsequent exposure study collected dust from the mattresses of young children in Thailand and Singapore [61]. Dust mite allergen in rural Thailand was less than in urban Singapore and positively correlated with air-conditioning use, while the endotoxin level in rural Thailand was higher (particularly in agricultural areas) compared to Singapore.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, house-dust and/or cockroach allergens represent another more widespread indoor air exposure across Thailand [80]. Sensitization to these allergens is very common in Asian countries, including Thailand [6061]. Some sources of indoor air pollution are also linked with outdoor air pollution and children tend to spend more time in indoors than outdoors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation